Βούβρωστις: interpretazione e fortuna di uno hapax omerico - Merisio, Elisa Nuria (Lexis, 2025)
This paper reconsiders the occurrences of the noun βούβρωστις in Greek literature starting from its first occurrence in Il. 24.532. On the basis of the presumable meaning of the term in a hexameter poem of the Hellenistic period (adesp. epic. fr. 4 Powell) and in a metrical inscription dated to the Imperial age (SGO 16/62/01) and taking into account pieces of evidence provided by Greek erudition, an interpretation of the term in the Iliadic passage different from the commonly accepted one is then proposed: instead of meaning ‘great hunger’ or ‘suffering’, the word refers to the personification of a malevolent deity.